EEG and Autonomic Responses During Performance of Matching and Non-Matching to Sample Working Memory Tasks with Emotional Content - Garcia, Ana; Uribe, Carlos Enrique; Tavares, Maria Clotilde; Tomaz, Carlos (Frontiers in Behavioral Neuroscience, 2011)
Working memory (WM) is a neural system responsible for the temporary storage of information and its utilization in problem solving. The central executive is theorized as the controller of storage functions that support WM. Neurophysiological data suggest that EEG theta and alpha oscillations in frontal and midline regions are involved in neural communication between the central executive and storage functions during WM performance. Emotion is known to modulate several memory systems, including WM, through central and peripheral pathways. However, the physiological correlations (electroencephalographic – EEG; autonomic nervous activity) of the effect of emotion over WM are not well described. In this study we aimed to identify physiological responses related to emotional WM performance. EEG (21 channels), heart rate (HR) and galvanic skin response (GSR) recordings were obtained from 54 volunteers while performing delayed matching and non-matching to sample tasks (DMTS/DNMTS). Emotional and neutral pictures from the International Affective Picture System and geometric figures were used as stimuli. As expected, WM performance was accompanied by presence of theta (frontal and midline electrodes) and Alpha power (parietal electrodes). Beta and gamma oscillations were concentrated in frontopolar and left temporal regions. DNMTS task was accompanied by increases in Beta power, HR and GSR compared to DMTS task. Correlation analysis showed a positive tendency for gamma in Fp2 site, ratio of LF/HF (HR low and high frequency) and skin conductance in both tasks. The HR results indicate an inverse reaction related to parasympathetic and sympathetic nervous system during the performance of the tasks. Taken together, our results contribute to elucidate the complex interactions between central and autonomic nervous systems in the modulation of emotional WM tasks.